Measuring energy-dependent photoelectron escape in microcrystals. (2020) - Storm, Selina L. S.; Crawshaw, Adam D.; Devenish, Nicholas E.; Bolton, Rachel; Hall, David R.; Tews, Ivo; Evans, Gwyndaf
No abstract available